GENETIC FOUNDATIONS OF THE BRONCHIAL ASTHMA - A.Yu. Asanov; L.S. Namazova; V.G. Pinelis; N.V. Zhurkova; N.I. Voznesenskaya (Union of pediatricians of Russia, 2008)
The article overviews the results of the studies of the genetic foundations of predisposition to the bronchial asthma. The authors provide detailed information on the molecular and genetic mechanisms of the bronchial asthma, roles performed by the polymorphisms of the interleukin genes and their receptors, IgE receptors, adrenergic receptors, CYS-LT enzymes in the pathogenesis of this disease, as well as their impact on the effectiveness of the drug therapy.Key words: bronchial asthma, genetic predisposition, pharmacogenetics.